EFL TEACHERS' UNDERSTANDING IN DEVELOPING LESSON PLAN - Putri, Annisa (2016)
EFL teachers' understanding in developing lesson plan is important to be investigated. Several studies revealed that EFL teachers' understanding in lesson plan development are unsatisfying. This study attempted to find out EFL teachers' undestanding of lesson plan and its development along with the problems the teachers faced in developing lesson plan. The researcher administered questionnaire, conducted interview, and analyzed the lesson plans developed by four EFL teachers to collect the data. The findings revealed that all participants understand and comprehend about the lesson plan suggested in Curriculum 2013. The findings also revealed that all participants understand about how to develop lesson plan by stating all elements of lesson plan in accordance with the requirements stated in the Regulation of Ministry of Education and Culture Number 103 year 2014. The problem found when the two teachers did not stated learning purposes. Even one of the teachers stated that learning indicator is similar with learning purposes. The problems also found when they were asked about the implementation of scientific approach, because it is new thing for them to apply the approach based on its stucture which consists of observing, questionning, collecting, associating and communicating. It also revealed that the teachers could not understand the system of learning assessment. The research concluded that the EFL teachers' understanding in developing lesson plan suggested in Curriculum 2013 is still need to be guided in order to be in accordance theoretically and fulfill the requirements of Ministry of Education and Culture.; pemahaman EFL guru dalam mengembangkan rencana pelajaran penting untuk diselidiki. Beberapa penelitian mengungkapkan bahwa pemahaman guru EFL dalam mengembangankan RPP tidak memuaskan. Penelitian ini berusaha untuk mengetahui pemahaman guru EFL dalam mengembangkan RPP dan masalah yang dihadapi. Peneliti menggunakan kuesioner, melakukan wawancara, dan menganalisis RPP yang dikembangkan oleh empat guru EFL guna mengumpulkan data. Hasil penelitian mengungkapkan bahwa semua peserta mengerti dan memahami tentang RPP yang disarankan dalam Kurikulum 2013. Temuan juga mengungkapkan bahwa semua peserta memahami tentang bagaimana mengembangkan RPP dengan menyatakan semua elemen rencana pelajaran sesuai dengan persyaratan yang tercantum dalam Peraturan Menteri Pendidikan dan Kebudayaan Nomor 103 tahun 2014. masalah ditemukan ketika dua guru tidak menyatakan tujuan pembelajaran. Masalah juga ditemukan ketika mereka ditanya tentang pelaksanaan pendekatan ilmiah, karena itu adalah hal yang baru bagi mereka untuk menerapkan pendekatan berdasarkan struktur yang yang terdiri dari mengamati, menanya, mengumpulkan, mengasosiasikan dan berkomunikasi. Hal ini juga mengungkapkan bahwa guru tidak bisa memahami sistem penilaian. Penelitian ini menyimpulkan bahwa pemahaman guru EFL dalam mengembangkan rencana pembelajaran yang disarankan dalam Kurikulum 2013 masih perlu dibimbing agar sesuai secara teoritis dan memenuhi persyaratan Departemen Pendidikan dan Kebudayaan.